Cell sources of inflammatory mediators present in bone marrow areas inside the meniscus. - Francisco Airton Castro Rocha; Virgínia Claudia Carneiro Girão; Rodolfo de Melo Nunes; Ana Carolina Matias Dinelly Pinto; Bruno Vidal; João Eurico Fonseca (PLoS ONE)
Purpose To demonstrate the production of inflammatory mediators by cells located in bone marrow spaces inside rodent menisci. Methods Mice subjected to transection of the medial collateral and anterior cruciate ligaments and meniscotomy (osteoarthritis model) or to a sham procedure, as well as non-operated (naive) mice and rats, had knee joints excised. Tissues were stained with hematoxylin-eosin and tartrate-resistant acid phosphatase (TRAP). CD68+ cells, inducible nitric oxide synthase (iNOS), interleukin (IL)-1β, and tumor necrosis factor (TNF) expression were detected using immunohistochemistry. Results Lamellar ossified areas, bone-entrapped osteocytes and bone marrow spaces were found inside menisci of one week up to 6 months-old naïve mice, regardless of gender. Menisci from naive rats also showed the same pattern with bone marrow areas. CD68+ cells were identified in bone marrow areas inside the meniscus of mice. TRAP+ osteoclasts, and hematogenous precursors expressing IL-1β, TNF, and iNOS were identified inside bone marrow areas in meniscal samples from both naïve and sham operated mice. Quantitative immunoexpression of IL-1 β, TNF and iNOS was more intense, P = 0.0194, 0.0293, 0.0124, respectively, in mouse knees from mice sacrificed 49 days after being subjected to an osteoarthritis (OA) model as compared to sham operated animals. Conclusion We provide novel data showing that rodent menisci display bone marrow areas with cells able to produce inflammatory mediators. Immunoexpression of inflammatory mediators in those bone marrow areas is significantly more pronounced in mice subjected to experimental OA.